PENINGKATAN PROFESIONALISME GURU DAN KUALITAS PEMBELAJARAN BIOLOGI DI SEKOLAH MELALUI LESSON STUDY (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2007)
This research was done to investigate impact of lesson study in order to improve teachers professionalism and the quality of teaching learning process in Biology. Although lesson study has been conducted since the year of 2005 at numerous schools- in Bandung, information on how far such activity does give impact to teacher as instructoi and teacher as observer has not been covered. The research was undertaken by spreading questions to the instructor as well as the observer. Furt5ermore, quaiity-of teaching learning process in the school was observed at SMP Lab. School and SMA Lab. School UPI. The research resulted in insight that through lesson study, teachers both served as instructor and observer can improve such competency as pedagogy, professional, personality, social as clearly inclicated in ., UU Guru dan Dosen l’,1o. 14 Tahun 2005″. However, for those teachers as observers, competency of pedagogy has not been significantly explored. Both the instructors and observers have not entirely user their KBM (teaching learning process) to conduct PTK (classroom action research). In uOOitionl the KBM ionducted in lesson study can improve quality of teaching leaming process in the classroom based upon good interaction between students and te;hers as well as among students (in or out the groups) during discussion and percentage of students who actively learned. Through model teaching learning pro”Jrr tleveloped in lesson study, students are trained to improve their ability i-n scientific work and to connect biology concept to its application in daily lile using local materials.
Keywords: Teacher’s professionalism; lesson study; KBM (Teaching learning process); PTK (Classroom action research)